Restoring paradise : rethinking and rebuilding nature in Hawaiʻi - Cabin, Robert J. (University of Hawaiʻi Press, 2013)
Three quarters of the U.S.'s bird and plant extinctions have occurred in Hawai'i, and one third of the country's threatened and endangered birds and plants reside within the state. Yet despite these alarming statistics, all is not lost: There are still 12,000 extant species unique to the archipelago and new species are discovered every year. This book shows why attempts to preserve Hawai'i's native fauna and flora require embracing the emerging paradigm of ecological restoration - the science and art of assisting the recovery of degraded species and ecosystems and creating more meaningful and sustainable relationships between people and nature. The author's extensive experience as a research ecologist and applied practitioner enables him to provide a rare, behind-the-scenes look at successful and inspiring restoration programs. He recounts Hakalau Forest National Wildlife Refuge's efforts to restore thousands of acres of degraded pasture on the island of Hawai'i back to the native rain forests that once dominated the area and sheltered native birds now on the brink of extinction. Along the way, he presents an overview of Hawaiian natural and cultural history, biogeography, and evolutionary biology. Following chapters look at restoration work underway by the U.S. Park Service to reestablish native species within the vast Hawai'i Volcanoes National Park; by a charismatic scientist and dedicated volunteers to restore the native forests of Auwahi on the southern slopes of Haleakalā; and by the Limahuli branch of Kauai's National Tropical Botanical Garden to revive a thousand-year-old taro plantation. To investigate the compelling and often conflicting philosophies and strategies of those involved in restoration, the author opens the third part of the book with interview excerpts from a cross-section of Hawai'i's environmental community. He concludes with a discussion of the contentious, evolving relationship between humans and nature and the power and limitations of science within and beyond Hawai'i.